Effect of Dietary Incorporation of Garlic (Allium sativum) and Turmeric (Curcuma longa) Powder and Their Combination on Feed Intake, Haemato-biochemical Parameters and Carcass Traits in Broiler Chicken - Ratika, Khwairakpam; Tiwari, D. P.; Mondal, B.C. (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to discern the effect of dietary incorporation of garlic and turmeric powder as feed additives on feed intake, haemato-biochemical parameters and carcass traits in Top 400 strain of broiler chicken. Day-old broiler chicks (n=120) were procured and randomly distributed into four treatment groups. Each treatment had three replicates with ten chicks in each replicate. The birds of control group (T1) were fed basal diet without any supplementation. In treatment groups T2, T3 and T4, basal diet wassupplemented with 3% garlic powder, 0.5% turmeric powder and 1.5% garlic powder plus 0.25% turmeric powder, respectively. The feed intake and growth performance in broiler chicks improved due to feeding of garlic incorporated diets. The haematological parameters were not affected due to dietary incorporation ofgarlic and turmeric. A significant (P